PENGARUH KEBIASAAN MEMBACA AL-QURA’AN TERHADAP KECERDASAN SPIRITUAL SISWA DI MTSN 2 KATINGAN - Mursyida, Hayatul; Yuliani, Anisa; Jannah, Miftahul; Aulia, Fatimatul (Program Studi PAI STAI Al Falah Banjarbaru, 2021)
Abstract: The habit of reading the Qur'an makes a person always remember Allah. By remembering Allah, a person will have peace of mind and a person who has peace of mind will think positively and behave well. Someone who thinks positively and behaves well is characteristic of someone who has spiritual intelligence. Therefore, the author conducted research on the effect of the habit of reading the Qur'an on the Spiritual Intelligence of Students at MTsN 2 Katingan.This study aims to determine the effect of the habit of reading the Koran on the spiritual intelligence of students at MTsN 2 Katingan. The hypothesis in this study is